The Potential of Fasting and Caloric Restriction to Mitigate Radiation Damage—A Systematic Review - Valayer, Simon; Kim, David; Fogtman, Anna; Straube, Ulrich; Winnard, Andrew; Caplan, Nick; Green, David A.; van Leeuwen, Flora H. P.; Weber, Tobias (Frontiers in Nutrition, 2020)
Detrimental health effects from ionizing radiation to the living being is one of the key concerns identified and addressed by Radiation Protection institutions, nationally and internationally on Earth and for human spaceflight. Thus, new methods for mitigating the adverse effects of ionizing radiation are urgently needed for terrestrial health and deep space exploration. Caloric restriction and (intermittent-) fasting have been reported to elicit a variety of immediate and long-term physiological effects. The rapidly growing body of evidence of research studies investigating the effects of caloric restriction and dietary fasting points towards a multitude of health benefits affecting numerous physiological systems. Therefore, a systematic literature review was performed to evaluate the evidence of caloric restriction and dietary fasting on the physiological response to ionising radiation in humans and animals. All experimental studies in humans, animals and eukaryotic cell lines available in PubMed, Cochrane library and specialised databases were searched comparing irradiation post-caloric restriction or fasting to a non-nutritionally restricted control group on a broad range of outcomes from molecular to clinical responses. The initial search yielded 2653 records. The final analysis included 11 studies. Most studies investigated the survival rate or cancer occurrence in animals. Included studies did not reveal any benefit from pre exposure caloric restriction, except when performed with post radiation caloric restriction. However, the effects of pre-exposure fasting suggest increased resilience to ionizing radiation.